2012
DOI: 10.1103/physrevb.86.075138
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric transmission in planar chiral split-ring metamaterials: Microscopic Lorentz-theory approach

Abstract: The electronic Lorentz theory is employed to explain the optical properties of planar split-ring metamaterials. Starting from the dynamics of individual free carriers, the electromagnetic response of an individual split-ring meta-atom is determined, and the effective permittivity tensor of the metamaterial is calculated for normal incidence of light. Whenever the split ring lacks in-plane mirror symmetry, the corresponding permittivity tensor has a crystallographic structure of an elliptically dichroic medium,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…The model is able to predict both field enhancement and transmission starting from an equation of motion of the individual electrons and can be applied for the homogenization of metamaterials. 32 The combination of controllable field concentration and total transmission paves the way for usage of metallic gratings for improvement of THz sources, detectors and sensors, as broadband polarizers and essentially for terahertz spectroscopy 33,34 and modulation applications. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The model is able to predict both field enhancement and transmission starting from an equation of motion of the individual electrons and can be applied for the homogenization of metamaterials. 32 The combination of controllable field concentration and total transmission paves the way for usage of metallic gratings for improvement of THz sources, detectors and sensors, as broadband polarizers and essentially for terahertz spectroscopy 33,34 and modulation applications. 35 …”
Section: Discussionmentioning
confidence: 99%
“…So, one arrives at a system of coupled equations for such a MM. The case of split-ring chiral MMs, where each unit cell consists of two ring segments, was considered in [7].…”
Section: Kinetic Equation For Electronsmentioning
confidence: 99%
“…Generalizing this model to describe the behavior of electrons in a more complex geometry such as an elementary cell of a MM is thus promising because it lets the effective properties of MMs be recovered ab initio. This approach was previously applied to planar chiral MMs where the elementary cell comprises two asymmetric ring segments [7]. It was shown that the resonance in the MM response appears due to two mutually opposing forces: (i) the Coulomb force from the charges at the tips of the ring segments; (ii) the electromotive force owing to the excited currents flowing along these segments.…”
Section: Introductionmentioning
confidence: 99%
“…Because polarization state is one of the essential properties for EM waves, the capability of manipulating the polarization state has been becoming one of the main interests. [13][14][15][16][17][18][19][20][21][22] One of the most effective approaches is to use chiral structures to acquire asymmetric transmission (AT) effect. [23][24][25][26][27][28] This AT effect is irrelevant to the nonreciprocity of the Faraday Effect in magnetooptical media, instead, originates from the interaction of EM radiation with the structural chirality of the two-dimension (2D) or three-dimension (3D) metamaterials.…”
Section: Introductionmentioning
confidence: 99%